2002
DOI: 10.2337/diabetes.51.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Suppresses Glucose-Stimulated Insulin Secretion by Affecting Post-Cytosolic [Ca2+] Elevation Signals

Abstract: The role of phosphatidylinositol (PI) 3-kinase in the regulation of pancreatic ␤-cell function was investigated. PI 3-kinase activity in p85␣ regulatory subunitdeficient (p85␣ ؊/؊ ) islets was decreased to ϳ20% of that in wild-type controls. Insulin content and mass of rough endoplasmic reticula were decreased in ␤-cells from p85␣؊/؊ mice with increased insulin sensitivity. However, p85␣؊/؊ ␤-cells exhibited a marked increase in the insulin secretory response to higher concentrations of glucose. When PI 3-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 81 publications
(93 reference statements)
8
64
1
Order By: Relevance
“…While -cell hyperplasia undoubtedly contributes to hyperinsulinemia in these genetically altered mice, this effect is variable and does not always correlate with the degree of hyperinsulinemia (Brüning et al 1997, Kido et al 2000. Most recently, Eto et al (2002) reported that islets isolated from mice deficient in the p85 regulatory subunit of PI3K exhibit augmented insulin secretory responses to glucose stimulation. These findings and the present studies suggest that a reduction in the negative feedback effect that insulin exerts upon its own secretion from the -cell (Iversen & Miles 1971, Ammon & Verspohl 1976, Liljenquist et al 1978, Ammon et al 1991 may play a role in their in vitro hypersensitivity to glucose and their in vivo development of hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…While -cell hyperplasia undoubtedly contributes to hyperinsulinemia in these genetically altered mice, this effect is variable and does not always correlate with the degree of hyperinsulinemia (Brüning et al 1997, Kido et al 2000. Most recently, Eto et al (2002) reported that islets isolated from mice deficient in the p85 regulatory subunit of PI3K exhibit augmented insulin secretory responses to glucose stimulation. These findings and the present studies suggest that a reduction in the negative feedback effect that insulin exerts upon its own secretion from the -cell (Iversen & Miles 1971, Ammon & Verspohl 1976, Liljenquist et al 1978, Ammon et al 1991 may play a role in their in vitro hypersensitivity to glucose and their in vivo development of hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with findings made using knockout mice where insulin signaling has been disrupted and by pharmacologic inhibition of kinases thought to be involved in insulin signaling. For example, islets deficient in the insulin receptor substrate-2 protein or the p85␣ regulatory subunit of phosphatidylinositol 3-kinase hyper-respond to glucose stimulation (41,44). Of particular physiologic significance, perhaps, is the observation that basal secretion is not augmented from these ␤-cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example the ␤IRKO and IRS-2 Ϫ/Ϫ mouse models developed diminished islet insulin content (11,16,18,20). Similarly, PI3-kinase regulatory subunit-deficient mouse islets also exhibited diminished insulin content (10). Several studies of insulinoma cells as well as primary islet cultures reported that insulin content was positively regulated by insulin signaling (6,43,(55)(56)(57)(58).…”
Section: Con(e)mentioning
confidence: 99%